Multichannel Analysis of Surface Waves for assessing soil stiffness - Elín Ásta Ólafsdóttir 1989- (2016)
Knowledge of the geotechnical properties of subsoil sites is essential in various civil engineering projects. Multichannel Analysis of Surface Waves (MASW) is a relatively new method where Rayleigh waves are generated and used to infer the shear wave velocity profile of the test site. Based on this the stiffness of the soil stratum can be estimated. MASW is a low-cost method. It is further non-invasive and environmentally friendly since it neither requires heavy machinery nor leaves lasting marks on the surface of the test site. Moreover, the MASW method provides information down to greater depth than SASW, a comparable method that until now has been applied in Iceland. MASW is divided into three steps: field measurements, dispersion analysis and inversion analysis. The main objective of this project is to develop and test a new set of software tools for analysis of MASW field data and to apply the methodology to estimate site-specific shear wave velocity profiles at Icelandic test sites. Results of field measurements carried out at two locations in South Iceland are presented to demonstrate the performance of the MASW software tools. The field measurements were performed using diverse receiver setups. The results indicate that the measurement profile configuration has significant effect on the quality of the acquired data and that it is beneficial to combine dispersion curves obtained from several different records prior to the inversion analysis. Validation of the field observations was done by comparison with results obtained by SASW and profiles estimated based on empirical correlations. Þekking á jarðtæknilegum eiginleikum setlaga og jarðvegsfyllinga, svo sem þykkt og stífni einstakra laga og heildarþykkt, er nauðsynleg í mannvirkjagerð. Fjölnemagreining á yfirborðsbylgjum (MASW) er nýleg aðferðafræði sem byggir á tvístrunareiginleikum yfirborðsbylgna í lagskiptum jarðvegi og tengslum á milli útbreiðsluhraða þeirra og fjaðureiginleika jarðvegs. Yfirborðsbylgjur eru framkallaðar með höggi á yfirborð ...